National Variations in Comorbidities, Glycosylated Hemoglobin Reduction, and Insulin Dosage in Asian Patients with Type 2 Diabetes: The FINE-Asia Registry. Issue 4 (December 2015) - Ji, Linong; Tsai, Shih-Tzer; Lin, Jay; Bhambani, Sanjiv
Abstract Introduction TheF irst BasalIn sulinE valuation (FINE) Asia study was a prospective, observational registry evaluating basal insulin initiation in Asian patients with type 2 diabetes mellitus inadequately controlled by oral antihyperglycemic agents. Methods The objective of this post hoc analysis was to observe and report the findings from individual participating countries. The primary endpoint was change in glycosylated hemoglobin (HbA1c ) from baseline to month 6 after basal insulin initiation. Secondary endpoints included change in fasting blood glucose (FBG), percent of patients achieving target HbA1c and FBG levels, average insulin doses, and hypoglycemic events. Results The study included 2921 patients from 11 Asian countries at baseline, 2679 (92%) of whom had evaluable data. Following initiation of basal insulin (neutral protamine Hagedorn insulin, glargine, or detemir), there was a significant (P < 0.001) difference in HbA1c reduction and proportions of patients meeting HbA1c and FBG targets (<7% and <110 mg/dL, respectively) across all country cohorts by month 6. Glycemic control also varied greatly, with 7.4% (Taiwan) to 71.5% (China) of patients reaching target HbA1c <7% levels. Mean (±standard deviation) insulin dose increases over the 6-month period ranged from 0.5 ± 3.1 U (Pakistan) to 6.0 ± 8.6 U (Thailand). Hypoglycemia rates also varied, with 7.1% (India) to 27.3% (China) of patients experiencing one or more events. Conclusions Data from the FINE-Asia registry study show widely varying degrees of baseline comorbidities and glycemic control in patients among the country cohorts observed. Countries with >9 years of diabetes prior to insulin initiation had the lowest reductions in HbA1c and proportions of patients achieving HbA1c and FBG targets, suggesting that earlier basal insulin initiation may afford better glycemic control in these patients. Funding This study was funded by Sanofi.